Ketogenic diet as a potential intervention for lipedema. (January 2021) - Keith, L.; Seo, C.A.; Rowsemitt, C.; Pfeffer, M.; Wahi, M.; Staggs, M.; Dudek, J.; Gower, B.; Carmody, M.
Highlights: Lipedema adiposity is resistant to weight loss diets, but may respond to ketosis. Ketogenic diets modulate pain in lipedema independent of weight loss. Ketogenesis positively impacts lymph vessel integrity and lymph transport. The release of BHB reduces inflammation by interrupting exogenous stressors. Abstract: Lipedema (LI) is a common yet misdiagnosed condition, often misconstrued with obesity. LI affects women almost exclusively, and its painful and life-changing symptoms have long been thought to be resistant to the lifestyle interventions such as diet and exercise. In this paper, we discuss possible mechanisms by which patients adopting a ketogenic diet (KD) can alleviate many of the unwanted clinical features of LI. This paper is also an effort to provide evidence for the hypothesis of the potency of this dietary intervention for addressing the symptoms of LI. Specifically, we examine the scientific evidence of effectiveness of adopting a KD by patients to alleviate clinical features associated with LI, including excessive and disproportionate lower body adipose tissue (AT) deposition, pain, and reduction in quality of life (QoL). We also explore several clinical features of LI currently under debate, including the potential existence and nature of edema, metabolic and hormonal dysfunction, inflammation, and fibrosis. The effectiveness of a KD on addressing clinical features of LI has been demonstrated in human studies, and shows promise as an intervention for LI. We hope this paper leads to an improved understanding of optimal nutritional management for patients with LI and stimulates future research in this area of study.